Small-scale woodland-based enterprises with outstanding economic potential: the case of honey in Zambia - Mickels-Kokwe, G. (Center for International Forestry Research, 2006)
In some countries, honey and beeswax are so important the term ‘beekeeping’ appears in the titles of some government ministries. The significance of honey and beeswax in local livelihoods is nowhere more apparent than in the Miombo woodlands of southern Africa. Bee-keeping is a vital source of income for many poor and remote rural producers throughout the Miombo, often because it is highly suited to small scale farming. This detailed Non-Timber Forest Product study from Zambia examines beekeeping’s livelihood role from a range of perspectives, including market factors, production methods and measures for harnessing beekeeping to help reduce poverty.The key aim of the study is to generate sufficient information and discussion on the bee-keeping or honey and beeswax industry to support efforts by government of Zambia to develop a beekeeping policy. The report presents initial findings from the beekeeping sector review. The report is structured as follows: Section 1 provides a general introduction, briefly describes the methodology used in the study, and outlines the critical questions, hypotheses and methodology. Section 2 discusses the bio-physical conditions for beekeeping and its relation to forest management. Section 3 provides an overview of the history of beekeeping, the commodity system, sector stakeholders and summarises the characteristics of the beekeeping industry in four case study Provinces, North-Western, Luapula, Central and Eastern Provinces. Section 4 gives insights into the honey marketing chain, from the primary producer to the exporter. Conclusions and recommendations are discussed in Section 5 and 6 respectively.